Impact assessment of wind power penetration on the operating reserve of the Luzon grid - Opiso, Dave Andrew E.
The possibility of high penetration of wind power in the Luzon Grid could impact the reliability of the power system due to the intermittent characteristics of wind resource. This study quantified the reliability performance of the Luzon Grid for various wind power penetrations based on the 2009 generation and demand of the grid. The probabilistic nature and variability of wind resource and the diurnal characteristics of the wind power plant site was modelled using the seven-hour sliding window approach to obtain the hourly equivalent forced outage rate of wind power (EFORW). This modeling technique for wind power made it adaptable to the well-established capacity outage probability model of conventional power plants. Thus, the reliability of the grid can be assessed by the loss of load expectation (LOLE) and loss of energy expectation (LOEE) based on chronological hourly available generation from conventional and wind power plants and the demand. This study has also determined the required additional operating reserve for various penetration of wind power to restore the chronological hourly system LOLE to the level where the grid has no wind power. Wind power in the Luzon Grid was found to have zero capacity credit because the wind power output can only displace the energy delivered by the conventional power plants. The additional operating reserve needed by the grid to maintain reliability is almost equal to the capacity of wind power.